2013
DOI: 10.1007/s10792-013-9775-x
|View full text |Cite
|
Sign up to set email alerts
|

Angle kappa changes after photorefractive keratectomy for myopia

Abstract: The goal of this study was to compare differences in the mean angle kappa and its intercepts before and after photorefractive keratectomy (PRK) for myopia. In a prospective controlled study, myopic patients were treated with aspheric wavefront-guided (personalized) PRK with a Bausch & Lomb Technolas 217z excimer laser. The manifest refraction, visual acuity, and angle kappa were evaluated preoperatively and at 1 and 6 months postoperatively. The same operator performed all angle kappa measurements using Orbsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Our results also show a positive correlation between lateral WTW and pupil diameter change. The related results have not been reported at home and abroad.This conclusion guides us to treat patients with large cornea during the operation to ruduce the dynamic changes in pupil size whit a darker environment as much as possible in order to improve the e ciency of pupil matching [26] .There is no correlation between the SE and the change of pupil diameter, but there is a negative correlation between the SE and Measured Centroid Shift.It has been reported in the literature that the refractive state has a signi cant correlation with the angle kappa, which is consistent with the results of this study [15] .Therefore, We speculate that the dynamic change of pupil center of Measured Centroid Shift is small for people with high myopia.Therefore, it can be understood that the dynamic change of angle kappa is correspondingly reduced, and the e ciency of pupil matching is higher. It is suggested that the proportion of compensating angle kappa vector is higher during operation.…”
Section: Discussionmentioning
confidence: 88%
“…Our results also show a positive correlation between lateral WTW and pupil diameter change. The related results have not been reported at home and abroad.This conclusion guides us to treat patients with large cornea during the operation to ruduce the dynamic changes in pupil size whit a darker environment as much as possible in order to improve the e ciency of pupil matching [26] .There is no correlation between the SE and the change of pupil diameter, but there is a negative correlation between the SE and Measured Centroid Shift.It has been reported in the literature that the refractive state has a signi cant correlation with the angle kappa, which is consistent with the results of this study [15] .Therefore, We speculate that the dynamic change of pupil center of Measured Centroid Shift is small for people with high myopia.Therefore, it can be understood that the dynamic change of angle kappa is correspondingly reduced, and the e ciency of pupil matching is higher. It is suggested that the proportion of compensating angle kappa vector is higher during operation.…”
Section: Discussionmentioning
confidence: 88%
“…[ 3 ] The range may slightly differ (4.97 ± 1.24°) if measured with the Orbscan IIz (Bausch and Lomb, USA). [ 10 ]…”
Section: Methodsmentioning
confidence: 99%
“…The kappa angle is generated by the intersection of the visual axis and the pupillary axis in the pupillary space. If the light re ex is in the nasal side, it is classi ed as positive; if it is in the temporal side, it is classi ed as negative [1][2][3]. The line perpendicular to the center of the corneal curvature at the entrance of the pupil is the pupillary axis, and the line joining the xation point and the fovea is the visual axis [3].…”
Section: Introductionmentioning
confidence: 99%